2018
DOI: 10.1002/mrm.27077
|View full text |Cite
|
Sign up to set email alerts
|

Development of methods and feasibility of using hyperpolarized carbon‐13 imaging data for evaluating brain metabolism in patient studies

Abstract: This study has presented the first application of hyperpolarized C metabolic imaging in patients with brain tumor and demonstrated the safety and feasibility of using hyperpolarized [1- C]pyruvate to evaluate in vivo brain metabolism. Magn Reson Med 80:864-873, 2018. © 2018 International Society for Magnetic Resonance in Medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
201
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 141 publications
(205 citation statements)
references
References 34 publications
4
201
0
Order By: Relevance
“…We have also applied the simulation framework for evaluating various analysis methods to other flip‐angle strategies, presented in the Supporting Information. The strategies presented there include a constant 10° for all time and metabolites, as well as a “multiband” 10° (pyruvate)–20° (lactate) strategy that has been used in several prostate and brain human HP pyruvate exams.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have also applied the simulation framework for evaluating various analysis methods to other flip‐angle strategies, presented in the Supporting Information. The strategies presented there include a constant 10° for all time and metabolites, as well as a “multiband” 10° (pyruvate)–20° (lactate) strategy that has been used in several prostate and brain human HP pyruvate exams.…”
Section: Resultsmentioning
confidence: 99%
“…MRI with hyperpolarized (HP) 13 C‐labeled substrates has emerged as an extremely promising metabolic imaging modality, because it can probe key metabolic pathways in patient studies. () These studies utilize dissolution dynamic nuclear polarization (DNP) to enhance the 13 C nuclear polarization, providing > 50 000 fold sensitivity increases in vivo. () The most promising HP substrate to date is [1‐ 13 C]pyruvate, which provides the following: monitoring of a key metabolic pathway, conversion to [1‐ 13 C]lactate, which is highly upregulated in most cancer types (the “Warburg effect”); high levels of polarization via dissolution DNP; and biocompatibility at doses of 0.43 ml/kg body weight and 250mM as determined in a Phase 1 safety trial .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development and in vivo implementation of dissolution DNP combined with 13 C MRSI has opened the door to noninvasive monitoring of real‐time cellular metabolism. Most notably, monitoring the conversion of hyperpolarized [1‐ 13 C]pyruvate to hyperpolarized [1‐ 13 C]lactate has recently been implemented in the clinic . Importantly, previous studies have shown that this metabolic reaction can serve as an early biomarker of response to therapy in a range of tumor types, including in orthotopic intracranial GBM models .…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary outcomes from Phase II patient studies further indicated that high k PL correlated very well with biopsy and pathological findings of aggressive human prostate cancer and poor response to therapy . Also, high lactate/pyruvate ratios were found in progressive glioblastoma …”
Section: Introductionmentioning
confidence: 95%